2012
DOI: 10.1007/s00464-012-2227-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy using a novel Single-Site® robotic platform: early experience from 45 consecutive cases

Abstract: Single-Site(®) is a new platform offering a potentially more stable and reliable environment to perform single-port cholecystectomy. Both simple and complicated cholecystectomies can be performed with safety. The technique is possible in patients with a high BMI. The induction of pneumoperitoneum using the new port and the docking process require additional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 13 publications
7
58
0
Order By: Relevance
“…The fourth issue are the postoperative hospital d. Konstantinos et al 12 reported that the mean PODs for SIRC were 23.84±10.27 h. Morel et al 21 reported mean PODs of 2.4 d. In this study, the PODs for all patients were 2.05±0.87 d (range: 1~4 d). However, in our study, the higher number of PODs after SIRC were not due to complications but to the insurance system, which offered inexpensive admission charges.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The fourth issue are the postoperative hospital d. Konstantinos et al 12 reported that the mean PODs for SIRC were 23.84±10.27 h. Morel et al 21 reported mean PODs of 2.4 d. In this study, the PODs for all patients were 2.05±0.87 d (range: 1~4 d). However, in our study, the higher number of PODs after SIRC were not due to complications but to the insurance system, which offered inexpensive admission charges.…”
Section: Discussionsupporting
confidence: 51%
“…This set of instruments is designed to be used with the Da Vinci Si Surgical System in single-incision surgery. 11,12 In SIRC, the flexible robotic arm crosses the other arm through the port, and the robot system electrically reverses the robotic arm to the right and to the left so that the surgeon's hand motion is natural. This electrical crossover helps the cholecystectomy to minimize the collision between the instruments through a 2 to 3 cm incision and the robotic system stably adjusts the camera and instruments during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Additionally the stable, 3-D operation field can enhance a surgeon' s ergonomic environment. This enables surgeons to avoid the situation of right and left disorientation for triangular configuration during laparoscopic single-port surgery.…”
Section: Potential Technique: Robotic Single Site Plus One Port Distamentioning
confidence: 99%
“…Moreover, there have been no severe complications, such as injury to the bile duct or conversion to laparoscopy or open surgery, 11,12 although one case of postoperative hemorrhage associated with SIRC has been reported. 13 Additionally, some authors have investigated cosmetic outcome and postoperative pain in comparative studies, 14,15 with less pain and better cosmetic outcomes occurring in SILC. 16,17 The results of the present study also showed good outcomes without any conversions or complications, even when no additional port was used during the procedure.…”
mentioning
confidence: 99%